PEMIKIRAN SEYYED HOSSEIN NASR: NILAI PENDIDIKAN ISLAM TRADISIONAL DITENGAH-TENGAH KEMODERNAN - Kulsum, Ummu (Fakultas Agama Islam Universitas Islam Madura, 2019)
Seyyed Hossein Nasr is one of the thinkers of religious theology, the most prominent contemporary Muslim thinker in the international world, who pays much attention to the problems of modern humans. His criticism of modern humans is quite sharp. The problems presented about modern Islam with strong arguments in resolving the problems of the people are one of the solutions offered, namely building traditional Islam. As a formulation of the problem raised is What is the concept of Nasr's thinking about traditional Islam? 2) Why did Nasr reject modernist Islam? 3) What is the analysis of Nasr's thinking about traditional Islam? while the method used is method literacy with a qualitative research approach. The analysis used is content analysis and descriptive analysis. The results of the discussion revealed about traditional Islam are more directed towards parennial philosophy while in the approach of Islamic teaching more focused on Sufism teachings, namely by starting from sharia, tariqat, essence and makrifat as a step towards God.